Wage Income Tax Reforms and Changes in Tax Burdens: 2000-2009 - Brys, Bert (OECD Taxation Working Papers, 2011)
The tax burden on labour and its evolution over time are issues that feature prominently in the political debate. Averaged across the OECD, personal income taxes, social security contributions and payroll taxes together account for more than 51% of total government revenues in 2008 (OECD, 2010). With tax burdens differentiated by earnings level and family situation, they serve a central role as redistribution policies. Importantly, by shaping both work incentives and the cost of labour, the level and structure of these taxes are major influences on the functioning of labour markets...